Pembentukan Negara Madinah - Miftahul Jannah Harahap; Evi Sukma Pratiwi (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
Together with the establishment of a pluralist state, the migration of the Prophet Muhammad SAW to Yathrib greatly influenced all communities in the country. The Prophet's role was very important in building the State of Medina as a political and religious representative chosen through negotiations who could build a society that could live tolerantly with various ethnic groups and customs. This research aims to explain the process of establishing the Medina state and the approach used. This research uses analytical study methods involving information gathering, source criticism and historiography. Thus, it can be concluded that the Prophet Muhammad was a leader who could produce a good transformation by building a new society in Medina, where people helped each other and tolerated each other without any differences.